Investigating The Writing Skills Of Freshman Turkish Language Teaching Students - Camurcu, Duygu (Selcuk Univ, Inst Turkish Studies, 2011)
The purpose of this study is to examine the first year students at Turkish Language Teaching department in terms at their expressions of thoughts and feelingsin writing. This study will not only draw attention to prospective Turkish language teachers' level of writing skills, but also will help to determine and solve problems. For this reason, in the 2009-2010 fall semester at the Turkish Lanuage Teaching department of the Educattion Faculty in Eastern Mediterranean University, 49 students were made to write two compositions about the topics they chose, in order to examine their writing skills. This study is a descriptive study in which the written compositions are analyzed considering the format, language and expression spelling and purctuattion criteria and evaluated within the scope of Yeni Ogretim Programina Gore Kuramdan Uygulamaya Turkce Ogretimi by Prof. Dr. Cemal Yildiz which took place in the book titled Yazili Anlatim Degerlendirme Formu.
Keywords: Writing skills; written expression; composition; Turkish educati